1980
DOI: 10.1002/app.1980.070250507
|View full text |Cite
|
Sign up to set email alerts
|

Membranes prepared from keratin–polyacrylonitrile graft copolymers

Abstract: SynopsisGraft copolymerization of acrylonitrile onto a soluble wool keratin derivative was studied with the reduced and carboxymethylated low-sulfur protein fraction from wool. Copolymerization was carried out under a variety of conditions with a redox system of ( N H~)~S~O B -N~~S O~ in 60% (w/w) aqueous ZnCl2 solution at 10°C. Monomer conversions higher than 90% were obtained by the stepwise addition of initiator. The graft products were successfully separated into grafted copolymer and homopolyacrylonitrile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Concerning the association between keratin and PAM or PAN, Schaller et al [147] described the preparation of composite membranes composed of Merino wool keratin and PAN, by graft polymerization of acrylonitrile (AN) onto a soluble keratin derivative. The authors, unfortunately, did not present any water adsorption data or thermomechanical characterization of the obtained composites [147].…”
Section: Polyacrylates Polyacrylonitrile (Pan) and Polyacrylamide (Pam)mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the association between keratin and PAM or PAN, Schaller et al [147] described the preparation of composite membranes composed of Merino wool keratin and PAN, by graft polymerization of acrylonitrile (AN) onto a soluble keratin derivative. The authors, unfortunately, did not present any water adsorption data or thermomechanical characterization of the obtained composites [147].…”
Section: Polyacrylates Polyacrylonitrile (Pan) and Polyacrylamide (Pam)mentioning
confidence: 99%
“…Concerning the association between keratin and PAM or PAN, Schaller et al [147] described the preparation of composite membranes composed of Merino wool keratin and PAN, by graft polymerization of acrylonitrile (AN) onto a soluble keratin derivative. The authors, unfortunately, did not present any water adsorption data or thermomechanical characterization of the obtained composites [147]. On the other hand, Samal et al performed the graft polymerization of acrylamide (AM) onto wool fibres and observed water adsorption, and the mechanical properties (both max load and strain) increased proportionally the grafting, whilst thermal properties had the opposite behaviour (proportional decrease with increasing grafting) [148].…”
Section: Polyacrylates Polyacrylonitrile (Pan) and Polyacrylamide (Pam)mentioning
confidence: 99%
“…A lot of studies have been focused on the combination of acrylonitrile‐based polymers and natural polymers. The strategies reported are mainly classfied into two ways: (a) graft‐polymerization of acrylonitrile onto casein,1–7 silk fibroin,8–10 wool keratin,11, 12 soybean protein,13, 14 gelatin15 etc., and (b) blending of ployacrylonitrile and silk fibroin,16–18 chitosan and its derivative 19–22…”
Section: Introductionmentioning
confidence: 99%
“…Functional molecules can be loaded on the keratin using thiol–ene click chemistry reactions . Schaller et al demonstrated the grafting of polyacrylonitrile on keratin surface which also shows that the keratin functional groups are readily available (after the reduction of disulfide bond) for further modifications …”
Section: Keratinmentioning
confidence: 99%